2018
DOI: 10.4103/0366-6999.233946
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Cardiopulmonary Resuscitation in Children of Asia Pacific

Abstract: Background:Recent advances in extracorporeal membrane oxygenation (ECMO) have led to increasing interest in its use during cardiopulmonary resuscitation (CPR). However, decisions regarding extracorporeal CPR (ECPR) in children are difficult as a result of limited studies, especially in Asia Pacific. The objective of this study was to investigate trends in survival and demographic details for children with ECPR in Asia Pacific recorded in the Extracorporeal Life Support Organization (ELSO) registry from 1999 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…[27] Five of the thirty included studies were studies examining data from the ELSO registry. [27,30,36,40,44] As such, the possibility of double counting patients from an institution that both published their results and reported the data to the ELSO registry exists. An additional sensitivity analysis was conducted to eliminate this possible bias by removing all ELSO registry studies and comparing these findings with the findings reported in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Five of the thirty included studies were studies examining data from the ELSO registry. [27,30,36,40,44] As such, the possibility of double counting patients from an institution that both published their results and reported the data to the ELSO registry exists. An additional sensitivity analysis was conducted to eliminate this possible bias by removing all ELSO registry studies and comparing these findings with the findings reported in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was also seen in pulmonary hypertension prior to ECPR (RR = 0.44 [0.12-1.61], I 2 = 0%, P = .22). Finally, the odds of SV physiology were not significantly different in the Alsoufi, B., 2014 [25] Saudi Arabia 2007-2012 39 14 41 IHCA R Anton-Martin, P., 2020 [26] USA 2000-2013 73 26 44 IHCA R Bembea, M., 2019 [27] USA 2000-2014 593 242 41 IHCA R Beshish, A., 2018 [28] USA 2005-2015 80 40 48 IHCA R Brunner, A., 2016 [29] Switzerland 2008-2014 19 NR 16 Both R Chen, G., 2018 [30] Asia Pacific 1999-2016 321 142 51 IHCA R Chrysostomou, C., 2013 [31] USA 2006-2010 40 15 75 NR R De Mul, A., 2019 [32] Switzerland 2008-2016 55 20 25 Both R Erek, E., 2017 [33] Turkey 2010-2014 25 NR 20 IHCA R Guo, Z., 2019 [34] China 2017 11 3 36 IHCA R Huang, S., 2012 [35] Taiwan 1999-2009 54 17 46 IHCA R Jolley, M., 2014 [36] Multi 1998-2013 293 121 36 IHCA R Kane, D., 2010 [37] USA 1995-2009 172 77 51 IHCA R KendIrlI, T., 2020 [38] Turkey 2014-2017 15 8 33 IHCA R Kramer, P., 2020 [39] Germany 2005-2016 72 34 36 Both R McMullan, D., 2014 [40] Multi 1998-2010 641 257 39 NR R Melvan, J., 2020 [41] USA 2002-2017 184 92 43 NR R Philip, J., 2014 [42] USA 2005-2012 59 NR 46 IHCA R Polimenakos, A., 2017 [43] USA 2007-2011 21 NR 62 IHCA R Raymond, T., 2010 [44] USA 2000-2007 199 75 44 IHCA R Shakoor, A., 2019 [45] USA 2010-2017 70 28 54 IHCA R Shin, H., 2016 [46] SK 2013-2016 12 6 33 NR R Sivarajan, V., 2011 [47] Australia 2002-2006 37 18 38 NR R Topjian, A., 2019 [48] Multi 2009-2015 157 57 46 IHCA R Torres-Andres, F., 2018 [49] USA 2007-2015 58 23 65.5 Both R Tsukahara, K., 2014 [50] Japan 2003-2012 21 8 14 Both R Walter, E., 2011 [51] Germany 1992-2008 42 19 40 IHCA R Wolf, M., 2012 [52] USA 2002-2011 90 NR 56 IHCA R Yates, A., 2019 …”
Section: Patient Significant Preexisting Complicationsmentioning
confidence: 99%